The sediment carbon stocks of intertidal seagrass meadows in Scotland. (5th September 2021) - Potouroglou, Maria; Whitlock, Danielle; Milatovic, Luna; MacKinnon, Gillian; Kennedy, Hilary; Diele, Karen; Huxham, Mark
Abstract: Seagrasses are highly productive ecosystems and hotspots for biodiversity, providing a plethora of benefits to the environment and to people. Their value in sequestering and storing carbon is increasingly being recognised, as the world searches for ways to mitigate the effects and slow the pace of climate change. However, many uncertainties remain, with basic information such as average carbon stocks, variability and species-specific differences missing for many regions. This study evaluates, for the first time, the carbon storage capacity of Zostera noltii and Zostera marina from intertidal seagrass meadows in Scotland. Sediment carbon stocks in the top 50 cm from vegetated and reference unvegetated plots were quantified at 10 estuaries distributed along the Scottish east and west coasts. The organic carbon stocks in the top 50 cm of the seagrass sediment ranged from a minimum of 14.94 Mg C ha −1 at the Moray Firth to a maximum of 105.72 Mg C ha −1 at the Firth of Forth, with a mean (±SD) of 54.79 ± 35.02 Mg C ha −1 across the 10 estuaries sampled. Moreover, seagrass areas showed enhanced carbon storage compared to reference unvegetated ones, however this was highly variable across depth, and among sites and estuaries. This paper addresses key gaps in knowledge concerning the role of intertidal Scottish seagrass meadows as carbon sinks and discusses the implication of this emerging information for their effective management and conservation. Highlights: The sediment carbon stocks of intertidal seagrass meadows were assessed in Scotland. Sediment carbon density was highly variable across depth and among sites. The sediment carbon stocks in the top 50 cm ranged from 14.94 to 105.72 Mg C ha −1 . Seagrass plots retained 20% more organic carbon (% DW) than unvegetated plots.